1986
DOI: 10.1111/j.1432-1033.1986.tb09353.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and complete primary structures of the heparin-, cell-, and DNA-binding domains of bovine plasma fibronectin

Abstract: The complete amino acid sequences of the heparin-, cell-and DNA-binding domains of bovine plasma fibronectin have been determined. The fragments were generated from the 170-kDa central plasmic fragment by extensive digestion with chymotrypsin, and they contain 268, 300 and 269 amino acid residues, respectively. No half-cystines or cysteines were found in these sequences. A glucosamine-based oligosaccharide group is attached to Asn-108 in the sequence of the DNA-binding domain. Only one of the three types of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 47 publications
(30 reference statements)
2
22
0
Order By: Relevance
“…The N‐terminal sequence of the 140 kDa fragment (VATSESVTE) was identical to the first nine residues of the 2 FnIII repeat of bovine fibronectin. The N‐terminal sequences of the 30 and 40 kDa fragments were identical (AVTTIPAP) and corresponded to the first eight residues of the 12 FnIII repeat module of the bovine fibronectin primary amino acid sequence (McDonagh et al ., 1981; Vibe‐Pedersen et al ., 1982; Skorstengaard et al ., 1982; 1984; 1986a, b; Petersen et al ., 1983).…”
Section: Resultsmentioning
confidence: 99%
“…The N‐terminal sequence of the 140 kDa fragment (VATSESVTE) was identical to the first nine residues of the 2 FnIII repeat of bovine fibronectin. The N‐terminal sequences of the 30 and 40 kDa fragments were identical (AVTTIPAP) and corresponded to the first eight residues of the 12 FnIII repeat module of the bovine fibronectin primary amino acid sequence (McDonagh et al ., 1981; Vibe‐Pedersen et al ., 1982; Skorstengaard et al ., 1982; 1984; 1986a, b; Petersen et al ., 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies have indicated that this segment contains a weak heparin and DNA binding site(s) (named Hep III domain), but its physiological relevance is unclear (13)(14)(15)(16). A recent study has proposed that the region comprising Fn repeats III1-7 may play a regulatory role in the process of matrix formation (26).…”
Section: Discussionmentioning
confidence: 99%
“…1 is a multidomain glycoprotein found in the plasma as an ϳ450-kDa disulfide-linked dimer and in the extracellular matrix (ECM), in the form of larger multimers (1,2). Structural variants of Fn arise from a single gene by alternative mRNA splicing and post-translational modification (3,4).…”
Section: Fibronectin (Fn)mentioning
confidence: 99%